Clinical simulations in emergency nursing cardiac emergencies - Emergency Nurses Association (Baltimore : Williams & Wilkins, 1997)
(Producer) Consists of 5 programs presenting pediatric, adult, and geriatric patients with various cardiac related emergency conditions, providing learning across the life-span. These simulations guide learners through all the steps involved in the emergency nursing process. Each case teaches quick reactions and provides problem-solving opportunities and is designed to maximize assessment skills by presenting symptoms and suggesting a number of possible diagnoses. Learners must observe the patients' symptoms and make both a primary and secondary assessment. The patient responds differently depending on the interventions chosen, giving learners the chance to see the outcome of their choices. In addition to clinical considerations, psychosocial needs of the patient and family are addressed
System requirements: IBM-PC or compatible computer, 486 33 MHz or faster CPU; 6-8 MB RAM (depending on program running); Microsoft Windows 3.1, 3.11, and Windows 95; SVGA display supporting at least 256 colors; double speed CD-ROM
Keywords: Heart Diseases -- nursing; Emergencies -- nursing